Effect of Dietary Oregano and Rosemary Essential Oil Supplementation on Growth Performance and Cecal Microbiota of Broilers - Cetin, E; Anar, B; Temelli, S; Cengiz, SS; Eren, M (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, the effect of dietary supplementation of oregano and rosemary essential oils (EO) on growth performance and cecal microbiota of broilers were investigated. A total of 450 1-d-old male Ross-308 broilers were divided into 5-experimental groups (10 replicates of 9 chickens): a Control (C), fed a basal diet; four treatments, which received a basal diet supplemented with oregano and rosemary EOs individually (O, 300 mg/kg oregano EO; R, 300 mg/kg rosemary EO) and combined (OR1, 150 mg/kg oregano EO + 150 mg/kg rosemary EO; OR2, 200 mg/kg oregano EO + 200 mg/kg rosemary EO). Body weight (BW), feed intake (FI), body weight gain (BWG), feed conversion ratio (FCR), and cecal microbiota (coliforms, clostridia and lactobacilli) were determined weekly, and at 42 d, respectively. BW in R (p<0.05) and OR2 (p<0.001), and BWG and FCR in OR2 (p<0.05) were significantly higher than C at 42 d, despite no difference in FI in any group during experimental period. Counts of cecal coliforms (p<0.001) and clostridia (p<0.01) decreased, and lactobacilli (p<0.001) increased substantially between C and treatment groups. Results indicated that combined oregano and rosemary EO (200 mg/kg ea) supplementation significantly increased BW and BWG, improved FCR in 1-42 d, lowered coliform and clostridial, and increased lactobacilli counts suggesting a beneficial shift in cecal microbiota.